Pendistribusian Dana Zakat , Infaq, dan Sedekeah (ZIS) dalam Memulihkan Perekonomian Mustahik Pasca Pandemi Covid-19 di Kota Makassar - Emily Nur Saidy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Covid pandemic had a negative impact on the MSME sector. Moreover, after COVID-19, MSMEs are facing the problem of rising prices, so they need additional capital to survive. The National Zakat Amil Agency (BAZNAS) of Makassar City, through its productive assistance program, is helping MSMEs to recover and improve their welfare as a result of the COVID-19 pandemic obtained from Zakat, Infaq, and Alms funds. This research aims to analyze the distribution of ZIS funds carried out by BAZNAS Makassar City and see the effectiveness of ZIS funds in restoring the mustahik economy after the Covid-19 pandemic. This research is qualitative research with a phenomenological approach. Determining the data source for respondents was carried out purposively. The results show that the distribution of ZIS funds after the pandemic is similar to during the pandemic. It's just that aid recipients have increased compared to after the pandemic. Distributing Zakat, Infaq, and Alms funds through productive assistance programs could be more effective in developing post-pandemic mustahik businesses.